Desarrollo de salchichas nutraceúticas con base a trucha arcoíris (Oncorhynchus mykiss) y corvina (Cynoscion) emulsificadas con quinua (Chenopodium) y garbanzo (Cicer arietinum) germinados - Guambuguete Sisa, Nelly Elizabeth (2025)
This research aimed to develop nutraceutical sausages based on rainbow trout (Oncorhynchus mykiss) and sea bass (Cynoscion nothus), emulsified with sprouted quinoa (Chenopodium quinoa) and chickpeas (Cicer arietinum). The nutritional profile of the raw materials was evaluated, determining that rainbow trout has a high omega3 content (31.99% polyunsaturated fatty acids), significantly surpassing sea bass (4.01%). Furthermore, germination increased the protein content of chickpeas (16.3%) and quinoa (12.4%). Through an experimental design and analysis of variance, the optimal formulation was identified (Treatment T2: 100% rainbow trout and sprouted chickpeas), which presented the highest levels of omega-3 (15.03%) and protein (13.10%). Sensory analysis demonstrated high acceptability of the T2 treatment, with excellent scores for color, odor, flavor, and texture. Additionally, the cost-benefit analysis confirmed the economic viability of this formulation. It is concluded that the development of this nutraceutical sausage is technically feasible, sensorially acceptable, and economically promising, offering a functional product with high added value, rich in essential fatty acids and high-quality proteins, which aligns with the current demand for healthy and functional foods.